Diversity of Non-Targeted Nematode, Bacteria and Microfungi Populations in Soil After Some Pesticide Treatment - Güven, Ayşenur; Koç, İbrahim (Van Yüzüncü Yıl Üniversitesi, 2020)
Agricultural areas are important ecological environments with chemical inputs via human intervention. The presence of this type of natural areas is important for human as well as other species. This research was conducted to determine the effects of Satellite 20 WP, Status 330 E, Pesos 100 EC and Pentran 22 E pesticides, which are widely used in agricultural fields of Bitlis, on non-target soil nematodes, aerobic mesophilic bacteria, microfungi populations and pH. The study was repeated (six times) according to variance analysis method (under in-vitro conditions). According to the variance analysis, the Period×Treatment interactions are important for pH, plant-parasitic and fungivore nematodes respectively (P=0.007; P=0.008; P=0.000), for omnivore-predator, bacterivore and total nematodes, on the other hand, (P=0.000; P=0.000; P=0.000) both period and the main effect of the treatments were statistically significant (P=0.046; P=0.017; P=0.009). Based on the profile analysis; pH increased especially in Satellite 20 WP treatment, although the number of aerobic mesophilic bacteria increased in the control treatment, it decreased in all pesticide treatments; the number of microfungi increased in Pesos 100 EC treatment but decreased in other treatments; plant-parasitic, fungivore and total nematode count decreased in all pesticide treatments; omnivore-predator and bacterivore nematodes were found to be partially affected. As a result, it has been determined that the used pesticides have positive or negative effects depending on the parameters considered.

Tarımsal alanlar, insan müdahalesi ile kimyasal girdilerin olduğu önemli ekolojik ortamlardır. Bu ortamların varlığı, insanlar için önemli olduğu kadar ortamı paylaşan diğer canlılar için de önemlidir. Bu araştırma, Bitlis İli tarımsal alanlarında yaygın kullanılan Satellite 20 WP, Status 330 E, Pesos 100 EC ve Pentran 22 E pestisitlerinin hedef olmayan topraktaki nematod, aerobik mezofilik bakteri, mikrofungus popülasyonları ve toprak pH’sına etkilerini belirlemek amacıyla yapılmıştır. Çalışma, in-vitro şartlarında tekrarlı ölçümlerde varyans analizi yöntemine göre altı tekerrürlü olarak yürütülmüştür. Yapılan varyans analizlerine göre Periyot×Uygulama interaksiyonlarının sırasıyla pH, bitki paraziti ve fungivor nematodlar için önemli olduğu (P=0.007; P=0.008; P=0.000), omnivor-avcı, bakterivor ve toplam nematodlar için hem periyot (P=0.000; P=0.000; P=0.000) hem de pestisit uygulamalarının ana etkisinin istatistiksel olarak önemli olduğu (P=0.046; P=0.017; P=0.009) bulunmuştur. Profil analizlerine göre; pH'ın, özellikle Satellite 20 WP uygulamasında artış gösterdiği aerobik mezofilik bakteri sayısının, kontrolde artmasına karşın tüm pestisit uygulamalarında azalma gösterdiği; mikrofungus sayısının, Pesos 100 EC uygulamasında artış göstermesine karşın diğer uygulamalarda azaldığı; bitki paraziti, fungivor ve toplam nematod sayılarının tüm pestisit uygulamalarında azaldığı; omnivor-avcı ve bakterivor nematodların kısmen etkilendiği görülmüştür. Sonuç olarak; kullanılan pestisitlerin, dikkate alınan parametrelere göre olumlu ya da olumsuz etkisinin olduğu belirlenmiştir.
Bazı Pestisit Uygulamalarından Sonra Toprakta Hedef Olmayan Nematod, Bakteri ve Mikrofungus Popülasyonlarının Değişimi
Keywords: Agricultural Engineering (Other); Ziraat Mühendisliği (Diğer)